Tipo de biofertilizante y mulch en las características agronómicas y el rendimiento en Coriandrum sativum L. en casa malla sombra. Loreto - Vargas Lozano, Mayra Alessandra (2025)
The objective of this research was to determine the interaction effects between the type of biofertilizer and the type of mulch on the agronomic characteristics and yield of Coriandrum sativum L. grown under shade mesh conditions in Loreto. A completely randomized factorial design (2×2) was used, with four treatments resulting from the combination of two biofertilizer types (liquid and solid) and two mulch conditions (with and without), with three replicates per treatment. Variables evaluated included plant height, plant width, root length, leaf weight, and total plant weight. The results showed highly significant effects of mulch (p<0.0001) and biofertilizer type (p<0.01) on most agronomic variables. The best performance was obtained with the liquid biofertilizer combined with mulch, achieving 28.2 cm in plant height, 24.8 cm in width, 9.4 cm in root length, and 188.35 g in leaf weight. It is concluded that the joint application of liquid biofertilizer and mulch significantly improves the agronomic development of coriander under protected conditions, constituting a viable and efficient agroecological strategy for agriculture in Loreto.